A generalisable methodology for stability assessment of walking aid users. (September 2017) - Costamagna, E.; Thies, S.B.; Kenney, L.P.J.; Howard, D.; Liu, A.; Ogden, D.
Highlights: We developed a novel method to assess stability of walking frame users. Our method considers user and device as a combined system. Our method uses the stability margin to inform on walking stability. Our method is generalisable to a range of walking aids. This work may impact on device design, prescription and user training. Abstract: To assist balance and mobility, older adults are often prescribed walking aids. Nevertheless, surprisingly their use has been associated with increased falls-risk. To address this finding we first need to characterise a person's stability while using a walking aid. Therefore, we present a generalisable method for the assessment of stability of walking frame (WF) users. Our method, for the first time, considers user and device as a combined system. We define the combined centre of pressure (CoPsystem ) of user and WF to be the point through which the resultant ground reaction force for all feet of both the WF and user acts if the resultant moment acts only around an axis perpendicular to the ground plane. We also define the combined base of support (BoSsystem ) to be the convex polygon formed by the boundaries of the anatomical and WF feet in contact with the ground and interconnecting lines between them. To measure these parameters we have developed an instrumented WF with a load cell in each foot which we use together with pressure-sensing insoles and a camera system, the latter providing the relative position of the WF and anatomical feet. Software uses the resulting data to calculate the stability margin of the combined system, defined as the distance between CoPsystem and the nearest edge of BoSsystem . Our software also calculates the weight supported through the frame and when each foot (of user and/or frame) is on the floor. Finally, we present experimental work demonstrating the value of our approach.